2020
DOI: 10.3390/molecules25246056
|View full text |Cite
|
Sign up to set email alerts
|

Protaetia brevitarsis seulensis Derived Protein Isolate with Enhanced Osteomodulatory and Antioxidative Property

Abstract: The osteogenic differentiation of stem cells is profoundly affected by their microenvironmental conditions. The differentiation behavior of stem cells can be tuned by changing the niche environments. The proteins or peptides that are derived by living organisms facilitate the osteogenic differentiation of stem cells. Here, we have evaluated the osteoinductive and antioxidative potential of the Protaetia brevitarsis seulensis insect-derived protein for human bone marrow-derived mesenchymal stem cells (hBMSCs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The media with only 5% FBS was taken as the control. The staining procedure was described in our previous studies. , Briefly, the cells were fixed with 3.7% paraformaldehyde (PFA) for 15 min at room temperature, followed by permeabilization with Triton-X 100 (0.1%) for 10 min. After that, the cells were blocked by 1% BSA for 1 h and incubated with specific primary and secondary antibodies against desmin and myogenin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The media with only 5% FBS was taken as the control. The staining procedure was described in our previous studies. , Briefly, the cells were fixed with 3.7% paraformaldehyde (PFA) for 15 min at room temperature, followed by permeabilization with Triton-X 100 (0.1%) for 10 min. After that, the cells were blocked by 1% BSA for 1 h and incubated with specific primary and secondary antibodies against desmin and myogenin.…”
Section: Methodsmentioning
confidence: 99%
“…PHs contain several bioactive peptides that act as stress-reducing agents. PHs can be obtained from various protein sources such as mushrooms, fish fins and scales, , porcine skin, soybeans, milk, , pigeon peas, potatoes, and edible insects . In addition, PHs (peptide fragments or cryptides) are widely recognized as antioxidative molecules present inside cells .…”
Section: Introductionmentioning
confidence: 99%
“…The popular ones include edible insects and marine organisms, among others (Van Huis, 2013). Recently, peptides from Protaetia brevitarsis insect‐derived protein have been shown to enhance osteogenic differentiation of bone stem cells in humans (Ganguly et al, 2020). In addition, algae and microalgae contain substantial amounts of proteins and are considered a sustainable protein sources for both human and animal nutrition (Nwachukwu & Aluko, 2021; Sheih et al, 2010).…”
Section: Sources and Isolation Of Food Proteins And Peptides With Ost...mentioning
confidence: 99%
“…In addition, the clinical studies have reported AG administration significantly improved the CD4+ lymphocyte count in HIV-positive patients [28] and inhibited the gp120-mediated cell fusion of HL2/3 cells with TZM-bl cells [29]. Moreover, publications related with the effects of natural molecules on osteogenesis of stem cells has been currently increased [30][31][32]. Stimulating bone and cartilage formation with biologically active pharmaceuticals derived from natural sources is a direction worth investigating for the treatment of homeostasis of bone diseases and/or bone remodeling in regenerative medicine field.…”
Section: Introductionmentioning
confidence: 99%